Prospects and development strategies of the restaurant industry at the regional level - Kovalchenko, K.; Sosyn, V. (Journal of Education, Health and Sport, 2024)
The article examines the prospects and development strategies of the restaurant industry at the regional level in Ukraine. Despite the challenges caused by military actions, the restaurant industry in Ukraine has shown remarkable resilience, as recent years have seen predominantly positive dynamics in the growth of new establishments. This indicates that the industry is recovering and is able to continue its development. The Ukrainian foodservice market has characteristic regional features. In some areas, the structure of visitors and target audiences changes, also the demand for restaurants in different segments shifts. There is an increasing demand for simpler and cheaper dishes, as well as a rise in the popularity of delivery services. In some regions, difficulties arise with the supply of key products for specialized establishments, leading to an increase in prices. In regions close to the combat zone, the foodservice market faces significant challenges, particularly due to shelling, infrastructure destruction, while in other areas, it recovers more quickly than in others. The development of the restaurant industry is crucial for the growth of the economy and the well-being of the population. Therefore, it is more important than ever to focus on promising areas for the development of the industry and with it to work out new strategies, considering modern challenges.